The Role of the University of Islam Nusantara in the Development of Environmental Conservation and Local Culture in the Agro-Edu-Tourism Geotheater - Pangestu, Aldi Putra; Herlingga, Muhammad; Nugroho, Iwan Satriyo; Susilowati, Desi; Rosmaladewi, Okke; Iriantara, Yosal; Ghaffar, Muhammad Andriana (Proceedings: International Seminar On Educational Studies, 2025)
This research examines the role of University of Islam Nusantara (Uninus) Bandung in developing environmental conservation and preserving local culture at the Geotheater Rancakalong Agroeduwisata in Sumedang Regency. The Geotheater, inaugurated in November 2020 and managed by BUMDesma Rusa Emas since December 2024, serves as an educational ecotourism center based on Sundanese culture, particularly thru the Ngalaksa ritual—an intangible cultural heritage representing the harmony between Nusantara Islam and Sundanese agrarian wisdom. Uninus, as an Islamic higher education institution based on the Ahlus Sunnah wal Jama'ah An-Nahdliyah values since its establishment in 1959, has partnered with Rancakalong thru the PTMGRMD, PKM, and KKN programs. However, its strategic role in ecological and cultural conservation has not been systematically and sustainably formulated. The research uses a qualitative approach with a participatory case study, collecting data thru in-depth interviews, observation, FGDs, and documentation in Sukamaju Village. The results show that the values of Nusantara Islam—such as rahmatan lil 'alamin, khalifah fil ardh, and gotong royong—are in line with the Ngalaksa philosophy and the principles of sustainable agro-ecotourism. Nevertheless, the collaboration between Uninus, BUMDesma, local government, and indigenous communities is still incidental. The research recommends a collaborative governance model that integrates the three pillars of higher education with local wisdom to strengthen Geotheater as a living lab for Nusantara Islamic civilization based on ecology, culture, and education.